Pilot study of random finger prick glucose testing as a screening tool for type 2 diabetes mellitus in the emergency department. Issue 10 (22nd September 2009) - Hewat, N; McD Taylor, D; MacDonald, E
Abstract : Background: A study was undertaken to determine the prevalence of undiagnosed hyperglycaemia among patients in the emergency department (ED) and to evaluate the usefulness of random fingerprick plasma glucose (RFPG) screening in the ED with GP follow-up. Methods: A cross-sectional pilot study of 101 non-diabetic patients in the ED aged ⩾45 years was performed. Results: 31 (30.7%) had never had diabetic screening. 67 (66.3%) had plasma glucose levels ⩾5.5 mmol/l and were advised to consult their GP; 38 (56.7%) did so and 23 (60.5%) of these had follow-up testing. Nine patients (8.9%) were ultimately diagnosed with impaired glucose metabolism. Conclusion: There is considerable potential for diabetic screening in the ED setting.